Glucose transporter 1 regulates the proliferation and cisplatin sensitivity of esophageal cancer. Issue 5 (5th April 2019) - Sawayama, Hiroshi; Ogata, Yoko; Ishimoto, Takatsugu; Mima, Kosuke; Hiyoshi, Yukiharu; Iwatsuki, Masaaki; Baba, Yoshifumi; Miyamoto, Yuji; Yoshida, Naoya; Baba, Hideo
Abstract: Glucose transporter 1 (GLUT1) expression is a prognostic marker for esophageal squamous cell carcinoma (ESCC). Recent work on GLUT1 and development of specific inhibitors supports the feasibility of GLUT1 inhibition as a treatment for various cancers. The anti–proliferative effects of GLUT1‐specific small interfering RNA (siRNA) and a GLUT1 inhibitor were evaluated in ESCC cell lines. Expression of pro–proliferative and anti–proliferative signaling and effector molecules was examined by western blotting and quantitative RT‐PCR. GLUT1 expression in pretreatment clinical biopsy samples was measured by immunohistochemistry and correlated with various clinicopathological parameters and response to chemotherapy. The reduction in standardized uptake value (SUV) of 18 F‐fluoro‐deoxyglucose was calculated using the formula: ([pretreatment SUVmax  – posttreatment SUVmax ]/pretreatment SUVmax ) × 100. GLUT1‐specific siRNA expression in ESCC cells inhibited their proliferation, increased expression of p27kip, and decreased expression of cyclin‐dependent kinase 6, pyruvate kinase muscle isozyme M2, lactate dehydrogenase A and phospho‐ERK1/2. Suppression of GLUT1 by siRNA increased low‐dose cisplatin‐induced inhibition of proliferation of TE‐11 ESCC cells, which express high GLUT1 levels. Similarly, BAY‐876, a GLUT1 inhibitor, enhanced cisplatin‐mediated inhibition of ESCC cell proliferation. GLUT1 expression in pretreatment biopsy samples was associated with the response to chemotherapy as well as the pathological tumor stage and histological response grade after esophagectomy. Finally, GLUT1‐negative tumors showed a significantly larger reduction in SUVmax (61.2% ± 4.5%) compared with GLUT1‐positive tumors (46.2% ± 4.4%). GLUT1 expression may be a surrogate marker of response to chemotherapy, and inhibition of GLUT1 may be a potential novel therapy for ESCC patients. Abstract : Recent work on GLUT1 and development of specific inhibitors supports the feasibility of GLUT1 inhibition as a treatment for various cancers. This study demonstrated that downregulation of GLUT1 expression had a strong anti–proliferative effect in ESCC cells and also improved their sensitivity to cisplatin. GLUT1 expression may be a surrogate marker of response to chemotherapy, and inhibition of GLUT1 may be a potential novel therapy for ESCC patients.